DISPARATE MODES OF RECOGNITION IN TRADITIONAL GRAPE-GROWING AND WINEMAKING IN SANTA CATARINA - Desplobins, Gérard; Lima da Silva, Aparecido (Science & Technology Journals, 2005)
Since the introduction of grapevines in the 19th century, Brazil's traditional winery system, based on inexpensive common wine, has changed only a little. This sector, with a dynamic based on quantity, has been compelled to adapt itself to market segmentation and to new quality demands. A tentative wine certification system was established in Santa Catarina, aiming to improve the quality of this type of wine. It relies on guaranteeing the technical and economic stability of the traditional system and is an original and well thought-out response to the risks of grape-growing techniques transferred from the European model, developed for high-quality wines and tending to cause standardization. The system of certification studded in this State has had difficulty in obtaining recognition of its quality levels, even with its roughly defined evaluation standards. Intended to compensate for the absence of government quality control for wines, it faces setbacks due to its lack of a conceptual and legal framework. Moreover, it has been appropriated by the industrial elite, which excludes most stakeholders involved and uses it to serve its own ends, thus impeding the intended quality improvement.